2004
DOI: 10.1038/sj.sc.3101646
|View full text |Cite
|
Sign up to set email alerts
|

Reused silicone catheter for clean intermittent catheterization (CIC): is it safe for spinal cord-injured (SCI) men?

Abstract: Study Design: Study of reusable catheter. Objective: To investigate whether a silicone cathether reused over years for clean intermittent catheterization (CIC) was safe for spinal cord injured (SCI) men. Setting: Maharaj Hospital, Chiang Mai, Thailand. Method: A cross-sectional study was obtained from SCI men who had used CIC with a reusable silicone catheter for more than a year. Demographic data, urological management and urinary tract complications focusing on the radiologic status of the urethra were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 8 publications
2
51
0
3
Order By: Relevance
“…Therefore, educating CIC patients on how best to decrease their risk of UTI is important and should be an ongoing mission, 24 in that, for instance, many times of CIC with keeping clean technique leading to low rate of frequency of UTI occurrence. 4,25,26 We did not show significant relationship between anticholinergics or other bladder pressure-decreasing-treatments and UTI occurrence, and it is considered the double treatments for low-compliance bladder by CIC and those drugs mutually operated and make analysis more complicated.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, educating CIC patients on how best to decrease their risk of UTI is important and should be an ongoing mission, 24 in that, for instance, many times of CIC with keeping clean technique leading to low rate of frequency of UTI occurrence. 4,25,26 We did not show significant relationship between anticholinergics or other bladder pressure-decreasing-treatments and UTI occurrence, and it is considered the double treatments for low-compliance bladder by CIC and those drugs mutually operated and make analysis more complicated.…”
Section: Discussionmentioning
confidence: 72%
“…Forty-nine patients completed a 12-month study, and the authors supported the use of hydrophilic-coated catheters, as they were associated with less hematuria and a decrease in the rate of UTIs. Interestingly, Kovindha et al 15 described the safety of long-term catheter reuse practices among individuals with SCI in Thailand. They reported an average usage time for each silicone catheter as~3 years (ranging from 1 to 7 years).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that single-use catheters may be reused if cleaned appropriately; however, these authors also cautioned that the reuse of catheters may be associated with increased risk of UTI. 15 Interestingly, others studies demonstrated that even microwaving of catheters up to 12 min was not sufficient to eradicate Pseudomonas aeruginosa or Staphylococcus aureus, although there was minimal change to the physical qualities of the catheter. 16 No studies, however, have attempted to directly examine the relationship between catheter reuse and UTIs, or what factors may influence this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that re-usable silicone catheters did not lead to increased urethral complications in 23 men but did lead to increased UT. 19 The average catheter use of a single catheter was three years. Therefore, this could be a method of bladder management in developing countries.…”
Section: Incidencementioning
confidence: 99%